Analysis of threshold values of contrast revealing coefficient in highway tunnel lighting. (October 2019) - Weng, Ji; Cai, Xianyun; Hu, Yingkui; Du, Feng
Highlights: The relationship between qc0 and minimum luminance threshold ΔL0 has been set up. ΔL0 under tunnel lighting environment can be determined with simulation experiments. qc0 can be determined based on the minimum luminance threshold ΔL0 . qc0 is the premise for subsequent studies. Abstract: Commission internationale de l'éclairage (CIE) defined the contrast revealing coefficient qc based on the perceived contrast method in highway tunnel lighting. Meanwhile, CIE recommended qc as an index in the lighting quality evaluation system. Several studies suggested that qc was 0.6 under counter-beam lighting and 0.2 under symmetric lighting in the threshold zone. However, there were no threshold values of the contrast revealing coefficient qc0 under different lighting systems (qc0 corresponds to the visual adaptation of human eyes). Thus, this study aimed to determine the threshold values of the contrast revealing coefficient qc0 based on small target visibility. The relationship between qc0 and minimum luminance threshold was established in tunnel lighting. Therefore, using the fixed value stimulation approach, the minimum luminance threshold and luminance contrast threshold could be determined under different background luminance and viewing angles. Moreover, based on the luminance contrast threshold, the threshold values of contrast revealing coefficient can be obtained under different lighting environments.